Characteristics of Lokodidi Formation Sandstone in Iloheluma Village, Gorontalo Regency - Aang Panji Permana; Alfi Ilda Sasmida; Ronal Hutagalung (Universitas Muhammadiyah Purwokerto, 2025)
This research is motivated by the absence of a detailed study of the characteristics of the Lokodidi Formation sandstone in the Keramat area of ​​Boalemo Regency, although the distribution of sandstone in this area has been identified in previous studies. The main problem raised is the lack of data on the geological setting and mineralogical and geochemical characteristics of the Lokodidi Formation sandstone, which are important for understanding the geological processes and resource potential in the area. The purpose of this study was to determine the geological setting of the research area and to analyze the characteristics of the Lokodidi Formation sandstone based on petrographic and geochemical data. The methods used include field surveys for sampling, geomorphological observations, and laboratory analysis in the form of thin section preparation for petrography and X-Ray Fluorescence (XRF) analysis to determine the content of the main and trace chemical elements in the sandstone. The classification of sandstone is carried out based on the Pettijohn scheme and the parameters of the SiO₂/Al₂O₃ and Fe₂O₃/K₂O ratios. The results of the study indicate that the geomorphology of the study area consists of three main units: denudational hills, volcanic hills, and alluvial plains. The stratigraphy of the study area consists of five rock units, namely fine sandstone, medium sandstone, coarse sandstone, breccia, and andesite. Petrographic analysis shows that the sandstone samples are dominated by the Lithic Arenite type, which is characterized by the composition of quartz, feldspar, and lithic fragments. XRF geochemical analysis identified the presence of two main types of sandstone, namely Fe-shale and Quartz Arenite, based on the different Fe and quartz contents in each sample. These findings enrich the understanding of the characteristics of the Lokodidi Formation sandstone and provide a basis for further research related to the geological potential and mineral resources in the area.